1997
DOI: 10.1002/cjce.5450750203
|View full text |Cite
|
Sign up to set email alerts
|

Liquid circulation and mixing in an inclined bubble column

Abstract: Gas and liquid velocities were measured in an inclined rectangular column, at inclinations in the range M 5 " and superficial gas velocities of 0.002 to 0.12 c d s . Liquid circulation was also characterized by measuring the time to mix a pulse of salt solution in the column. Inclining the column by up to 10" from the vertical induced a drastic change in behavior, from a bubble column with evenly distributed gas bubbles to a segregated system with rapid liquid circulation pumped by rising gas bubbles. The liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
1
5
1
Order By: Relevance
“…Moreover, a secondary flow in the liquid phase, induced by the rising bubbles, with the liquid phase flowing upward with the bubbles on the one side of the column and downward at the column’s opposite side, has been reported, indicating a strong drag-based interaction in the hydrodynamics of the two-phase flow system. This latter observation is confirmed by Lu et al who measured the influence of the inclination angle on the bubble rise velocity. These authors observed an influence of the inclination angle on the bubble rise velocity only in their multibubble flow tests, whereas due to lack of bulk liquid circulation and in accordance with Masliyah et al, no significant dependency on vessel slanting was observed for the single-bubble rise tests.…”
Section: Introductionsupporting
confidence: 73%
“…Moreover, a secondary flow in the liquid phase, induced by the rising bubbles, with the liquid phase flowing upward with the bubbles on the one side of the column and downward at the column’s opposite side, has been reported, indicating a strong drag-based interaction in the hydrodynamics of the two-phase flow system. This latter observation is confirmed by Lu et al who measured the influence of the inclination angle on the bubble rise velocity. These authors observed an influence of the inclination angle on the bubble rise velocity only in their multibubble flow tests, whereas due to lack of bulk liquid circulation and in accordance with Masliyah et al, no significant dependency on vessel slanting was observed for the single-bubble rise tests.…”
Section: Introductionsupporting
confidence: 73%
“…5a 1 -a 4 are contour plots of local streamwise gas velocities as a function of vessel inclination. Gas velocity in the upper-wall region increased with increasing vessel tilt angle thus reinforcing the liquid bulk circulation [10]. It can also be seen in Fig.…”
Section: Static Columnmentioning
confidence: 66%
“…To the best of the authors' knowledge, despite the growing significance of petroleum FPSO applications and potential on-board installation of multiphase reactors, investigations on flow dynamics of floating bubble columns is a virgin field of research. There are a few studies in the literature, which exclusively tackled hydrodynamic issues arising from static inclined bubble columns [9,10]. So far, only floating packed beds and fluidized beds received somewhat more coverage.…”
Section: Introductionmentioning
confidence: 99%
“…The Reynolds number associated with the mean velocity of the liquid and the gap thickness of the channel is less than 1000 so that (based on single-phase flow criteria) the flow is expected to be laminar. Buoyancydriven flows due to small mis-alignments are known to be important in bubble columns (Lu et al 1997) and fluidized beds (Couderc 1985). In addition, the segregation and buoyancy-driven flows have a strong influence on oil and natural gas wells, which typically involve two or three phases (oil, gas and water) and are drilled at an angle to the vertical.…”
Section: Introductionmentioning
confidence: 99%